Executive Committee Minutes 2018-04-12 - Academic Senate:::::::::
Agenda – Approved. Minutes - 3/29/18 – Approved. Chair Report. Provost Report. Statewide Senate Report. Vice Chair Report. Schedule and discuss time for LMS discussions at Senate on 5/3 and 5/17. From FSAC: Policy for Periodic Evaluation of Athletic Coaching Faculty: Criteria, Procedures, and Forms – approved for the Senate agenda. From FSAC: Revision to Periodic Evaluation of Temporary Faculty – approved for the Senate agenda. Senate Snacks. Vice President of Administration and Finance Report. EPC Report. SAC Report. CFA Report. Associated Students Report. Senate agenda approved.